Efektivitas Penerapan E-Performance di Kelurahan Gunung Anyar Tambak Kota Surabaya - Ridho Ainur Rasyidin; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
E-Performance is a performance management information system that evaluates the performance of civil servants and serves as a guide in granting additional performance money. One of a government who implementing e-Performance is Kelurahan Gunung Anyar Tambak, Surabaya City. Implementation of e-Performance in Kelurahan Gunung Anyar Tambak Surabaya city starting since 2016, there is no research that assesses how effective the implementation of e-Performance in Kelurahan Gunung AnyarTambak Surabaya City. Therefore, this study aims to determine the effectiveness of the implementation of e-Performance based on four aspects of e-Performance assessment, namely aspects of cost, quality aspects, time aspects, and aspects of work behavior. This research is descriptive research with quantitative approach. This research uses saturated sampling technique in which all members of the population are used as members of the research sample. The total sample in this research were 8 person, they are civil servant in Kelurahan Gunung Anyar Tambak Surabaya City. Data collection techniques in this research using questionnaires and interviews and data analysis techniques using quantitative and descriptive analysis technique. The conclusion of this research is implementation of e-Performance is effective. This result can be proven from two aspects which are categorized quite effective, these aspects are cost aspect and quality aspect, while aspects of time and aspects of work behavior are considered effective. Based on the assessment of respondents, the effectiveness of the implementation of eperformance can be said to be effective.